RETRACTED ARTICLE: Intravenous lidocaine improves postoperative cognition in patients undergoing laparoscopic colorectal surgery: a randomized, double-blind, controlled study - Xian-xue Wang; Jing Dai; Qi Wang; Hui-wei Deng; Yun Liu; Gui-fan He; Hua-jing Guo; Ya-lan Li (BMC Anesthesiology)
Abstract Background The risk of postoperative cognitive dysfunction(POCD) in laparoscopic surgery should not be overlooked. Intravenous lidocaine can reduce perioperative inflammatory response in patients undergoing laparoscopic surgery, while the effect of intraoperative intravenous lidocaine on postoperative cognitive function in patients undergoing laparoscopic colorectal cancer surgery has not been well studied. We investigated whether intraoperative lidocaine improves postoperative cognitive function after laparoscopic radical resection for colorectal cancer. Methods We conducted a prospective, randomized double blinded controlled trial to investigate the effect of intravenous lidocaine on rapid postoperative recovery in patients undergoing laparoscopic radical resection of colorectal cancer. The patients were randomly assigned to receive either intravenous lidocaine or saline. The primary outcome was cognitive dysfunction defined by a decrease from pre- to postoperative ≥ 2 of the Mini-Mental State Examination (MMSE) score, at the 3rd and the 7th postoperative days. Secondary outcomes were the MMSE raw score and parameters of the patients’ postoperative recovery such as agitation and length of stay in the post-anaesthesia care unit (PACU), length of hospital stay, markers of inflammation (white blood cell count and CRP), and incidence of complications. Results Seventy-three patients in the lidocaine group and 77 patients in the control group completed the trial. The rate of cognitive dysfunction was lower in the lidocaine group than that in the control group, both at the 3rd (18.57% vs. 63.64% for each group respectively; RR = 0.26, 95%CI = 0.19–0.32; p < 0.0001) and at the 7th postoperative day (12.33% vs. 53.25% for each group respectively; RR = 0.28, 95%CI = 0.22–0.35; P < 0.001). The postoperative MMSE scores were also higher in the lidocaine group than in the control group both at the 3rd (median 25 vs. 24 respectively) and at the 7th postoperative day (26 vs. 24 respectively). Also, patients in the lidocaine group displayed a lower white blood cell count than the control group at the 1st postoperative day (8.5 ± 2.7 vs. 10.4 ± 3.3; p < 0. 001). No differences were evidenced for the other secondary outcomes. Conclusions Intraoperative intravenous lidocaine can significantly improve postoperative cognitive function in patients undergoing laparoscopic radical resection of colorectal cancer. Trial registration Chinese Clinical Trial Registry (16/1/2022, registration number: ChiCTR2200055683)